Gene expression analysis of the ribosomal protein gene, RPL 14 in cell lines derived from human nasopharyngeal epithelium - Vasudevan, Lisha (Universiti Malaysia Sarawak (UNIMAS), 2015)
Ribosome is an essential cellular organelle that is responsible in protein production. Many ribosomal proteins (RP) are involved in various roles besides protein biosynthesis, called extraribosomal functions. Ribosomal protein genes are associated with many genetic diseases and cancers. Previous studies have revealed difference in RP regulation of nasopharyngeal carcinoma (NPC) cell lines compared to the normal nasopharyngeal epithelium cell line. However, there has been no literature to date on the association between RPL 14 and nasopharyngeal carcinoma. Hence, in this study relative expression pattern of RPL 14 in NPC cell line, HKI, compared to the normal nasopharyngeal epithelium cell line, NP69 was observed using molecular technique such as Reverse Transcriptase Polymerase Chain Reaction CRT-PCR). This study revealed specific PCR product with the estimated size of 773 bp for RPL 14. RPL 14 did not show differential expression in NPC; but this does not suggest that it is not associated with nasopharyngeal carcinoma.